1961
DOI: 10.4141/cjss61-022
|View full text |Cite
|
Sign up to set email alerts
|

Sulphur Fractions of Legumes as Indicators of Sulphur Deficiency

Abstract: and the total nitrogen-total sulphur ratio also showed differences, their magnitude was not of the same order as with these two fractions.Similar determinations for red clover showed the diiTerences to be smaller than for alfalfa and alsike clover and they appear ro be of doubtful value for predicting the need for sulphur fertilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

1962
1962
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 5 publications
1
8
0
Order By: Relevance
“…Some N uptake was increased by N fertilizer and some available soil N (Nuttall, 1984). Addition of S fertilizer greatly assisted in this process as has been found by others (Bardsley and Jordan, 1957;Cairns and Carson, 19fl;Dijkshoom et a!., 1960;Walker and Bentley, 1961). The additional N uptake because of the application of + 0.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Some N uptake was increased by N fertilizer and some available soil N (Nuttall, 1984). Addition of S fertilizer greatly assisted in this process as has been found by others (Bardsley and Jordan, 1957;Cairns and Carson, 19fl;Dijkshoom et a!., 1960;Walker and Bentley, 1961). The additional N uptake because of the application of + 0.…”
Section: Discussionmentioning
confidence: 60%
“…wh,~n fertilizers are applied to the same stand over a period of years on soils of northern Saskatchewan. Because N to S ratios in herbage tissue have been used as an index of S availability by several researchers (Aulakh et al, 1976;Bardsley and Jordan, 1947;Dijkshoorn et al, 1960;Walker and Bentley, 1961;Westermann, 1975), a comparison of these ratios in relation to soil tests (Nuttall, 1984) might be useful in improving S fertilizer recommendations. The removal ofN, P, and S nutrients from the soil by alfalfa herbage in relation to what is applied by fertilizer may be a useful in<licator of the amount of nutrients required by the plant and that being maintained in the soil.…”
mentioning
confidence: 99%
“…The small response of aspen seedling growth rates to S application indicates that the two aspens were not very sensitive to S availability, perhaps because of a low S requirement by the two aspens. In agronomic crops, S appeared to be more deficient than P in those types of soils (Newton 1936;Walker and Bentley 1961). Our data set shows that when S was applied together with P, the effects were greater than if S was applied alone for most of the measured growth parameters.…”
Section: Aspen Growthmentioning
confidence: 52%
“…Earlier studies have shown that Luvisolic soils are deficient in P and S needed for the growth of various plant species (e.g., Newton 1936;Walker and Bentley 1961;Toogood et al 1962). Earlier research on the nutrition of poplar and aspen species had focused on N, P, and micronutrients and had shown strong growth response to N, P, or other nutrient additions at planting (Heilman and Xie 1993;van den Driessche 1999;Brown and van den Driessche 2002).…”
Section: Introductionmentioning
confidence: 98%
“…(11), and sugarbeets (Beta vulgaris L.) (10) have also been reported. However, not all studies are in agreement (2, 18,22), and recently the constancy of the (N/S)p ratio has been questioned (9,15).…”
mentioning
confidence: 99%